2014
DOI: 10.4081/rg.2014.5441
|View full text |Cite
|
Sign up to set email alerts
|

The Cephalonia, Ionian Sea (Greece), sequence of strong earthquakes of January-February 2014: a first report

Abstract: On 26.1.2014 and 3.2.2014 two strong earthquakes of M w 6.0 and M w 5.9 ruptured the western Cephalonia Isl., Ionian Sea (Greece), at the SSW-wards continuation of the Lefkada segment of the Cephalonia Transform Fault Zone (CTFZ), causing considerable damage and a variety of ground failures. High-precision relocation of the aftershocks implies that the seismogenic layer was of 35 km in length (L) striking NNE-SSW, of 10 km maximum in width and 15 km in thickness. Two aftershock 2014 earthquakes ruptured on lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 26 publications
3
33
0
2
Order By: Relevance
“…Today's rockfall hazard issues and estimation of the risk of rock fall are considered essential. Recent earthquakes in Alkyonides islands (Marinos et al, 1986), Parnitha Mt (Pavlides et al, 2002), Movri Mt (Koukouvelas et al, 2010, Lefkada (Papathanassiou et al, 2013) and Cephalonia island (Papadopoulos et al, 2014) showed that Greek type earthquakes are usually accompanied by small to large scale slope instabilities, including commonly rockfalls. Taken together the recent impacts of ground shaking in Greece and the preliminary results from two areas of high seismic risk we identify that the method used can give reliable results.…”
Section: Discussion and Conclusive Remarksmentioning
confidence: 99%
“…Today's rockfall hazard issues and estimation of the risk of rock fall are considered essential. Recent earthquakes in Alkyonides islands (Marinos et al, 1986), Parnitha Mt (Pavlides et al, 2002), Movri Mt (Koukouvelas et al, 2010, Lefkada (Papathanassiou et al, 2013) and Cephalonia island (Papadopoulos et al, 2014) showed that Greek type earthquakes are usually accompanied by small to large scale slope instabilities, including commonly rockfalls. Taken together the recent impacts of ground shaking in Greece and the preliminary results from two areas of high seismic risk we identify that the method used can give reliable results.…”
Section: Discussion and Conclusive Remarksmentioning
confidence: 99%
“…The relocated hypocentral depth is estimated to 16.5 km , while its aftershock distribution occurred above the focal depth having a rather steep, E-dipping trend . The proposed moment tensor by Papadopoulos et al (2014) shows an almost pure strike-slip, ESE-dipping fault plane (strike/dip/rake = 023°/68°/175°; Figure 2). The second strongest event (Mw5.3, NOA) occurred almost 5 hours after the first one at a relocated depth of 12.5 km.…”
Section: The 2014 Cephalonia Earthquake Sequencementioning
confidence: 99%
“…Unfortunately, the aftershock sequence of this event could not be isolated because it overlapped with the mainshock's aftershock sequence. The moment tensor proposed by Papadopoulos et al (2014) reveals a pure reverse, ENE-dipping fault (strike/dip/rake = 352°/40°/89°; Figure 2). …”
Section: The 2014 Cephalonia Earthquake Sequencementioning
confidence: 99%
See 1 more Smart Citation
“…The second significant EQ, M w = 5.9, hereafter also referred to as "EQ2", occurred on the same island on 3 February 2014 (03:08:45 UT), with epicentre at (38.25 • N, 20.40 • E) and a depth of ∼ 10 km. Various studies of the two earthquakes have already been published, indicating their seismotectonic importance (Karastathis et al, 2014;Valkaniotis et al, 2014;Papadopoulos et al, 2014;Ganas et al, 2015;Sakkas and Lagios, 2015;Merryman Boncori et al, 2015) as they were located on two different active faults that belong to the same seismic source zone.…”
Section: Introductionmentioning
confidence: 99%